Why Do Some Young Adults Not Graduate from Upper Secondary School? On the Importance of Signals of Labour Market Failure - Björn Anders Gustafsson; Katarina Katz; Torun Österberg (Institute for the Study of Labor (IZA), 2016)
In high-income countries, not completing secondary school often entails a high risk of social exclusion. Using data on young adults born in 1985 that grew up in metropolitan Sweden, we study factors associated with not graduating from upper secondary school at age 21. Our hypothesis is that if a young person sees examples of people who are not able to earn a living despite having a long education, such negative examples are influential. Results from estimated logistic models are consistent with the hypothesis.
Keywords: D64; I24; R23; 330; secondary schooling; Sweden; social exclusion; neighbourhoods